Perbedaan Gula Darah Sewaktu Pada Pasien Diabetes Mellitus Tipe 2 Sebelum Dan Sesudah Pemberian Totok Punggung - Lie Liana Fuadiati; Eka Mei Dianita; Ananda Patuh Padaallah (Malahayati Nursing Journal, 2025)
ABSTRACT A problem that often arises from patients is blood sugar instability. Currently, in addition to pharmacological treatment (medical drugs), non-pharmacological therapy and alternative therapies are widely developed. Not to replace medical treatment, but used as a support for medical treatment. One of the non-pharmacological therapies is back acupressure. The purpose of this study was to determine the average random blood sugar in patients with type 2 diabetes mellitus before and after back acupressure and to determine whether there was a difference in random blood sugar in patients with type 2 diabetes mellitus before and after back acupressure. Experimental design research design, using one group pretest-posttest control group design. The sample in this study were 35 diabetes mellitus. The sampling technique used purposive sampling with inclusion and exclusion criteria determined by the researcher. The measuring instrument in this study used a glucometer which functions to measure blood sugar levels. Data analysis in this study used the Wilcoxon-test, because the data was not normally distributed. The results of this study were that the average blood sugar levels of respondents before the intervention were 234 mg/dL and the average blood sugar levels of respondents after the intervention were 223 mg/dL. The results of the statistical test analysis using the Wilcoxon pre-post blood sugar test for patients with diabetes mellitus obtained sig. (tailed) or a p value of 0.000 α, which means that H1 is accepted or there is a difference in the average between before and after the intervention. Back acupressure helps improve blood circulation and stimulates organs that play a role in sugar metabolism, thereby helping to lower blood sugar levels. It can be concluded that there is a difference in blood sugar levels when patients with diabetes mellitus before and after back acupressure is given. Keywords: Random Blood Sugar Levels, Back Acupressure.  ABSTRAK Masalah yang seringkali muncul dari pasien adalah ketidakstabilan gula darah. Saat ini selain pengobatan farmakologis (obat-obatan medis), terapi non farmakologis dan terapi alternatif banyak dikembangkan. Bukan untuk menggantikan pengobatan medis, namun digunakan sebagai pendukung pengobatan medis. Salah satu terapi non farmakologis yaitu totok punggung. Tujuan dari penelitian ini adalah mengidentifikasi rerata gula darah sewaktu pada pasien diabetes mellitus tipe 2 sebelum dan sesudah pemberian totok punggung dan mengetahui adakah perbedaan gula darah sewaktu pada pasien diabetes mellitus tipe 2 sebelum dan sesudah pemberian totok punggung. Desain penelitian experimental design, menggunakan one group pretest-posttest control group design. Sampel pada penelitian ini adalah 35 pasien diabetes mellitus. Teknik Sampling menggunakan purposive sampling dengan kriteria inklusi dan eksklusi yang ditentukan peneliti. Alat ukur pada penelitian ini menggunakan glucometer yang berfungsi untuk mengukur kadar gula dalam darah. Analisis data pada penelitian ini menggunakan Wilcoxon-test, dikarenakan data tidak berdistribusi normal. Hasil penelitian pada penelitian ini adalah rerata kadar gula darah responden sebelum intervensi rata-rata 234 mg/dL dan rata-rata gula darah responden sesudah intervensi 223 mg/dL. Hasil analisis uji statistik menggunakan Uji Wilcoxon pre-post gula darah pasien diabetes mellitus diperoleh sig.(tailed) atau nilai p sebesar 0,000 α, yang berarti H1 diterima atau ada perbedaan rata-rata antara sebelum dan sesudah diberikan intervensi. Totok punggung membantu meningkatkan sirkulasi darah dan merangsang organ-organ yang berperan dalam metabolisme gula, sehingga membantu menurunkan kadar gula darah. Dapat disimpulkan bahwa ada perbedaann gula darah sewaktu pasien diabetes mellitus sebelum dan sesudah pemberian totok punggung. Kata Kunci: Kadar Gula Darah Sewaktu, Totok Punggung.